CuO-CeO₂ Photocatalysis for the Degradation of Remazol Textile Dyes - Rositasari, Putri Redita; Pramesti, Thineza Ardhea; Rachmanto, Tuhu Agung; Amalia, Aussie (Universitas Diponegoro, 2025)
Water pollution, particularly from textile industry waste, has become an increasingly significant environmental issue. Textile waste, especially synthetic dyes, contributes substantially to water pollution because of its complex structure and low biodegradability. Dyes such as Remazol Brilliant Red and Remazol Turquoise Blue, which are commonly used in the textile industry, are stable, toxic, and difficult to degrade biologically. One promising approach to address this issue is photocatalysis using photocatalysts such as CuO and CeO₂, which possess high degradation capabilities for organic contaminants. This study explored the effectiveness of CuO-CeO₂-based photocatalysts in degrading Remazol Turquoise Blue and Remazol Brilliant Red dyes. Photocatalysts were synthesized with varying CuO-CeO₂ concentrations, and degradation tests were conducted using UV light to observe dye degradation. The results show that the CuO-CeO₂ photocatalysts at a concentration of 25% achieved the highest degradation efficiency, with nearly 41.5% removal of Remazol Turquoise Blue and 26.1% removal of Remazol Brilliant Red after 120 min. Increasing the photocatalyst concentration increases the number of active sites, accelerating the degradation process. However, there is a limitation at very high concentrations because of the potential for catalyst particle agglomeration.